1987
DOI: 10.1137/0908049
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Iterative Methods as Applied to the Solution of the Nonlinear Three-Dimensional Groundwater Flow Equation

Abstract: This paper compares the efficiency of seventeen different methods for the solution of the simultaneous nonlinear finite difference approximating equations for groundwater flow in a watertable aquifer in three dimensions. Solution methods include those of Newton, Picard, and generalized linear methods. The Newton and Picard iteration methods were implemented by making use of several different linear methods including successive overrelaxation, the strongly implicit procedure, and eight different preconditioned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 9 publications
0
24
0
Order By: Relevance
“…Relative efficiency of the Newton and Picard methods seems to be problem specific (Kuiper, 1987;Mehl, 2006). There is evidence that the Newton method performs better for highly nonlinear problems when combined with relaxation schemes and residual control (Cooley, 1983;Jacobs, 1988;Press, 2007).…”
Section: Newton Linearization Methodsmentioning
confidence: 99%
“…Relative efficiency of the Newton and Picard methods seems to be problem specific (Kuiper, 1987;Mehl, 2006). There is evidence that the Newton method performs better for highly nonlinear problems when combined with relaxation schemes and residual control (Cooley, 1983;Jacobs, 1988;Press, 2007).…”
Section: Newton Linearization Methodsmentioning
confidence: 99%
“…Complex DNAPL distribution patterns have been observed in case studies (see e.g. Feenstra and Cherry , 1988; Cherry , 1987), laboratory experiments ( Kueper et al , 1989; Schwille , 1988) and through detailed numerical simulations of DNAPL migration in random spatially correlated permeability fields ( Kueper and Frind , 1990). An erratic, imperfectly known source location combined with poorly defined dissolution kinetics that further depend on local groundwater velocities affected by heterogeneity is likely to lead to pump‐and‐treat remediation uncertainties far greater than those predicted by current groundwater quality optimization models.…”
Section: Uncertainty and Risk Associated With Plume Prediction And Aqmentioning
confidence: 98%
“…The iteration methods that are generally used are the Picard and Newton algorithms. Theoretically, Newton's method converges one order of magnitude faster than the Picard scheme [19], but several studies have shown that this method is inferior to the Picard method [44,65,66]. Newton's method converges quadratically only in the vicinity of the solution.…”
Section: Iterative Procedures and Adaptive Time-steppingmentioning
confidence: 99%